Constant Switching Frequency For Direct Torque Control Of Induction Motor - Siti Azura, Ahmad Tarusan; Yusnida, Ahmad Tarmizi; Auzani, Jidin; Kasrul, Abdul Karim; Huzainirah, Ismail; R., Sundram; Muhd Khairi, Abd Rahim (Institute Of Electrical And Electronics Engineers Inc. (IEEE), 2016)
DTC drives utilizing hysteresis comparator is one of the simplest and most popular technique used in induction drives. However, due to its disadvantage of variable switching frequency causes serious problem in DTC especially for electromagnetic torque ripple. This paper proposed a technique of constant switching that could reduce the ripple on both torque and phase current for DTC by using triangular waveform or carrier frequency. Thus, the conventional and proposed DTC will be simulated and demonstrated by using Altera field-programmable gate array (FPGA) and digital signal processor. Simulation results presented in this paper shows the torque and stator current ripple with the proposed DTC algorithm when varying the speed and the carrier frequency.